Perception of First-Time Voters among Students of Madrasah Aliyah Negeri (MAN) 1 Cirebon City in Election Socialization Through The 2023 Election Parade - Romlah, Siti; Wildanu, Eka; Abijaya, Sastra (ann4publisher@gmail.com, 2025)
Backgroud. This research is to find out and describe the perceptions of novice voters of Madrasah Aliyah Negeri (MAN) 1 Cirebon City school students in electoral socialization through the 2023 election parade. Methods.The research uses a descriptive qualitative approach research method using Bimo Walgito's Perception theory which has several sub-focuses namely absorption of stimuli or objects from outside the individual, understanding, assessment and evaluation. Data collection methods are observation, interviews and documentation. The number of informants was 15 people. Result. Based on the research results, it shows that MAN 1 Cirebon City students have high enthusiasm in participating in election outreach through the 2023 election parade.Students can find out about the various ballot papers, what is voted on, the importance of elections and practice voting procedure simulations. Students also assessed that the socialization was educational and provided insight regarding the election. Conclusion. It can be concluded that the perception of beginner voters at Madrasah Aliyah Negeri (MAN) 1 Cirebon City in the implementation of socialization is quite effective which aims to increase knowledge and introduce elections to students who have a role as beginner voters among students. Implementation. Of course, this can increase the participation of novice voters themselves who are generation Z by preparing them as intelligent voters who can influence choosing the best future.